Richard H.M. Settle correspondence and photograph - Settle, Richard H. M.
Letters and typewritten transcripts of letters written by Settle during three voyages aboard whaling ships from New Bedford, Mass., including the Charles W. Morgan to the Indian Ocean, the A.R. Tucker to the Atlantic Ocean, and the Bounding Billow to the Pacific Ocean. His letters are written to Georgeanna, or Georgia, in New Bedford, who became his wife after the first voyage. The letters discuss life at sea and provide details about whaling.
Whaler.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Settle, Georgeanna -- Correspondence; A.R. Tucker (Bark); Bounding Billow (Bark); Charles W. Morgan (Ship); Seafaring life; Whaling -- Atlantic Ocean; Whaling -- Massachusetts -- New Bedford; Whaling -- Indian Ocean; Whaling -- Pacific Ocean; New Bedford (Mass.) -- History; Whalers (Persons)